#Justice4Marielle: memory, datafication and justice among digital counterpublics that name Marielle Franco - Josiowicz, Alejandra; Deusdará, Bruno; Summers, Edward (Revista da ABRALIN, 2024)
This article seeks to examine the digital discursive practice of naming Marielle Franco on Twitter, mobilizing the perspectives and theoretical framework of Digital Humanities in the Global South, Data feminism and Datafication from Below. We also employ the methodology and theoretical framework of Digital Discourse Analysis and Critical Technocultural Discourse Analysis, integrating aspects of Performance Studies and Gender Studies to explore the relevance of memory and performance for contemporary digital counterpublics. We advance a technocultural discourse analysis of tweets that reference Marielle Franco between 2018 and 2023, in Spanish, English and Portuguese. We use a combination of techniques of computational textual analysis implemented in Wolfram Mathematica to study the chronological distribution of tweets; the emergence and relevance of hashtags; the users that were most frequently mentioned and the different topics they mobilised in social networks. Our conclusions point to the digital technocultural discourse on Marielle Franco as practices of memory and mourning that contribute to constitute a digital counterpublic in which naming, together with practices of datafication from below, are highly political, and serve not only to reassert collective identity but also to create a vocabulary to speak about the intersectional nature of oppression.